THE ANTHROPOMORPHIC-BASED CHARACTER IN THE ANIMATION FILM “AYO MAKAN SAYUR DAN BUAH” - Pebriyanto, Pebriyanto; Ahmad, Hafiz Aziz; Irfansyah, Irfansyah (Capture : Jurnal Seni Media Rekam, 2022)
Children are arguably less motivated to consume vegetables. At the same time, animated films as learning media are considered effective in evoking emotion and influencing the audience. Consequently, the Ministry of Health of the Republic of Indonesia created the animated film "Ayo Makan Sayur dan Buah" as a campaign to encourage children to consume vegetables. This study seeks to determine the visuals of animated vegetable characters used to motivate children to consume vegetables. This qualitative research employed a case study method referring to the manga matrix theory and the anthropomorphic approach in design review as a data analysis technique. This study's anthropomorphic approach indicates that the design of vegetable characters in the animated film "Ayo Makan Sayur dan Buah" has not been fully optimized to evoke children's emotions because it is still influenced by other verbal messages in the film.